Methodical Recommendations for writing of case report on infectious diseases - Ryabokon, E. V.; Onischenko, T. Ye. (Zaporozhye state medical university, 2008)
In the guidelines for writing a history of infectious diseases for the 5th year students of the Medical Faculty the modern international classification of infectious diseases, examples of the formation of clinical diagnosis, given modern standards laboratory examination according to clinical protocols, laboratory parameters are norms and basic characteristics diet.